Les femmes et les enfants d’abord - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Prince Agyirey-Kwakye, du Youth Club for Nature Conservation, qui œuvre pour le respect de l’environnement (YCNC, PO Box AD 130, Cape Coast, C/R, Ghana ; E-mail : ycnc@hotvoice.com), nous décrit Nutrition for Quality Health (NQH), l’initiative...